Ultralow 192 Hz RF linewidth optoelectronic oscillator based on the optical feedback of mode-locked laser diodes - Haji, M.; Hou, L.; Kelly, A.; Akbar, J.; Marsh, J.; Arnold, J.; Ironside, Charlie (2012)
We present an ultralow RF linewidth (192 Hz) and subpicosecond phase noise (260 fs) using a passively mode-locked quantum-well laser with feedback via a dual optical fiber loop.